A comprehensive characterization of acute heart failure with preserved versus mildly reduced versus reduced ejection fraction – insights from the ESC‐HFA EORP Heart Failure Long‐Term Registry. (10th January 2022) - Kapłon‐Cieślicka, Agnieszka; Benson, Lina; Chioncel, Ovidiu; Crespo‐Leiro, Maria G.; Coats, Andrew J.S.; Anker, Stefan D.; Filippatos, Gerasimos; Ruschitzka, Frank; Hage, Camilla; Drożdż, Jarosław; Seferovic, Petar; Rosano, Giuseppe M.C.; et al.
Abstract : Aims: To perform a comprehensive characterization of acute heart failure (AHF) with preserved (HFpEF), versus mildly reduced (HFmrEF) versus reduced ejection fraction (HFrEF). Methods and results: Of 5951 participants in the ESC HF Long‐Term Registry hospitalized for AHF (acute coronary syndromes excluded), 29% had HFpEF, 18% HFmrEF, and 53% HFrEF. Hospitalization reasons were most commonly atrial fibrillation (more in HFmrEF and HFpEF), followed by ischaemia (HFmrEF), infection (HFmrEF and HFpEF), worsening renal function (HFrEF), and uncontrolled hypertension (HFmrEF and HFpEF). Hospitalization characteristics included lower blood pressure, more oedema and higher natriuretic peptides with lower ejection fraction, similar pulmonary congestion, more mitral regurgitation in HFrEF and HFmrEF and more tricuspid regurgitation in HFrEF. In‐hospital mortality was 3.4% in HFrEF, 2.1% in HFmrEF and 2.2% in HFpEF. Intravenous diuretic (∼80%) and nitrate (∼15%) use was similar but inotrope use greater in HFrEF (16%, vs. HFmrEF 7.4% vs. HFpEF 5.3%). Weight loss and estimated glomerular filtration rate improvement were greater in HFrEF, whereas reduction in natriuretic peptides was similar. Over 1 year post‐discharge, events per 100 patient‐years (95% confidence interval) in HFrEF versus HFmrEF versus HFpEF were: all‐cause death 22 (20–24) versus 17 (14–20) versus 17 (15–20); cardiovascular (CV) death 12 (10–13) versus 8.6 (6.6–11) versus 8.4 (6.9–10); non‐CV death 2.4 (1.8–3.1) versus 3.3 (2.1–4.8) versus 4.5 (3.5–5.9); all‐cause hospitalization 48 (45–51) versus 35 (31–40) versus 42 (39–46); HF hospitalization 29 (27–32) versus 19 (16–22) versus 17 (15–20); and non‐CV hospitalization 7.7 (6.6–8.9) versus 9.6 (7.5–12) versus 15 (13–17). Conclusion: In AHF, HFrEF is more severe and has greater in‐hospital mortality. Post‐discharge, HFrEF has greater CV risk, HFpEF greater non‐CV risk, and HFmrEF lower overall risk. Abstract : Acute heart failure in patients with preserved (HFpEF), mildly reduced (HFmrEF) and reduced ejection fraction (HFrEF): admission profiles, in‐hospital treatment and outcomes.